Analisis Kualitatif Kandungan Formalin dan Boraks pada Daging Ayam Di Beberapa Pasar Makassar - Husain, Halimah; jumrah, elfira (Illea : Journal of Health Sciences, Public Health and Medicine, 2025)
This study aims to qualitatively analyze the presence of formalin and borax in chicken meat sold in several traditional markets in Makassar City. The method used is a qualitative test using specific reagents for detecting formalin and borax on five chicken meat samples randomly collected from five different markets. The results show that no borax was detected in any of the tested samples. However, four out of five chicken meat samples were found to contain formalin. These findings indicate that there are still vendors or producers using hazardous substances that are prohibited in food processing. This highlights the need for increased supervision by relevant authorities and public education on the dangers of consuming food products containing harmful chemicals. This study is expected to serve as a reference for policymaking to ensure food safety in Makassar City.